54 Sacubitril–valsartan (LCZ 696) improves longitudinal strain and ejection fraction in preclinical models treated with doxorubicin through NLRP3, MyD88, and pro-fibrotic chemokines. (8th December 2021) - Quagliariello, Vincenzo; Buccolo, Simona; Iovine, Martina; Maurea, Fabrizio; Rea, Domenica; Barbieri, Antonio; Maurea, Nicola
Abstract: Aims: Doxorubicin-mediated adverse cardiovascular events are among the leading causes of morbidity and mortality in breast cancer patients. Sacubitril–valsartan (LCZ 696) is a combination drug, made up of neprilysin inhibitor sacubitril and angiotensin II receptor blocker valsartan, used for the treatment of heart failure in patients with a reduced ejection fraction. We hypothesized that LCZ 696, administered during doxorubicin, could improve cardiac function and cardiac inflammation in preclinical models. Methods: Human Foetal cardiomyocytes (HFC cell line) were exposed to subclinical concentration of doxorubicin (200 nM) alone or in combination with LCZ-696 (100 mM) for 72 h. After the incubation period, we performed the following tests: cell viability, apoptosis and necrosis; expression of malondialdehyde and 4-hydroxynonenal and concentration of intracellular Ca2+. Moreover, pro-inflammatory studied were also performed (activation of NLRP3 inflammasome; expression of TLR4/MyD88; mTORC1 Fox01/3a; NF-κB). C57Bl/6 mice were untreated (Sham, n = 6) or treated for 10 days with doxorubicin i.p. at 2.17 mg/kg (DOXO, n = 6), LCZ-696 at 60 mg/kg (LCZ, n = 6) or doxorubicin combined to LCZ-696 (DOXO-LCZ, n = 6). Ejection fraction, radial and longitudinal strain were analysed through transthoracic echocardiography (Vevo 2100). Cardiac tissue expression of NLRP3 inflammasome, Myd88, NF-kB, and 13 chemokines (IL-1α, IL-1β, IL-2, IL-4, IL-6, IL-10, IL-12, IL17-α, IL-18, IFN-γ, TNF-α, G-CSF, and GM-CSF) were quantified. Results: LCZ-696 exerts cardioprotective effects, enhancing cell viability of 48–54.6% compared to only doxorubicin-treated cells ( P < 0.001 for all); LCZ 696 decreased NLRP3, MyD88 and NF-kB expression in cardiac cells. In preclinical study, LCZ 696 improved significantly the EF and prevented the reduction of radial and longitudinal strain after 10 days of treatment with doxorubicin. A reduced expression of NLRP3, MyD88 and NF-kB in cardiac tissues was seen in DOXO-LCZ group compared to DOXO mice ( P < 0.001). Cardiac expression of IL-1β, IL-6, TNF-α, G-CSF and GM-CSF were significantly reduced after treatment with LCZ-696 indicating anti-inflammatory properties. Conclusions: LCZ-696 exerts direct beneficial effects in cardiomyocytes exposed to doxorubicin. In preclinical models, LCZ-696 reduced inflammation and cytokine expression involved in doxorubicin-mediated cardiotoxicity.